Regulation of Ptch1 by miR-342-5p and FoxO3 Induced Autophagy Involved in Renal Fibrosis - Tang, Simin; Wang, Yi; Xie, Guiling; Li, Wenjun; Chen, Yanna; Liang, Jinshu; Liu, Pei; Song, Fuhu; Zhou, Jun (Frontiers in Bioengineering and Biotechnology, 2020)
The pathogenesis of renal fibrosis (RF) is not well understood. Here, we performed an integrative database analysis of miRNAs and mRNAs to discover the major regulatory pathway in RF. Putative miRNAs and mRNAs involved in RF in unilateral ureteral obstruction (UUO) model mice were extracted and analyzed using the Gene Expression Omnibus (GEO) database. The bioinformatics analysis suggested that Ptch1 expression is regulated by miR-342-5p and FoxO3. Then real-time PCR, Western blot, Fluorescence in situ hybridization were done to confirm the hypothesis. Sixty-three differentially expressed miRNAs (DE-miRNAs) in GSE118340, 141 DE-miRNAs in GSE42716, and 183 DE-mRNAs in GSE69101 were identified. Various bioinformatic analyses revealed miR-342-5p as a strong candidate regulator in RF. We also predicted that miR-342-5p targets Ptch1 and that FoxO3 is the transcription factor of Ptch1. We also observed that TGF-β1 upregulated the expression of miR-342-5p and inhibited the expression of FoxO3 and Ptch1 in TCMK-1 cells. Furthermore, downregulation of miR-342-5p reversed the inhibitory effect of TGF-β1 on the expression of Ptch1 in TCMK-1 cells, while downregulation of FoxO3 promoted the inhibitory effect of TGF-β1 on the expression of Ptch1. Additionally, downregulation of Ptch1 increased TGF-β1-induced autophagy, as evidenced by an increase in the number of GFP-LC3 puncta and the increased protein expression of SOSTM1/p62 and LC3II/LC3I. Our findings showed that Ptch1 expression is negatively regulated by miR-342-5p and positively regulated by FoxO3, and downregulation of Ptch1 induced autophagy in TGF-β1-stimulated TCMK-1 cells. These findings will further our understanding of the molecular mechanisms of RF and provide useful novel therapeutic targets for RF.